Free radical scavenging potency of quercetin catecholic colonic metabolites: Thermodynamics of 2H+/2e− processes. (1st March 2017) - Amić, Ana; Lučić, Bono; Stepanić, Višnja; Marković, Zoran; Marković, Svetlana; Dimitrić Marković, Jasmina M.; Amić, Dragan
Graphical abstract: Highlights: Catecholic metabolites possess higher radical scavenging potency than quercetin. They have potential to inactivate free radicals of different characteristics. Second HAT and SPLET mechanisms enable this potency. Abundant colonic metabolites could be at least in situ efficient antioxidants. Direct free radical inactivation by metabolites may be of biological significance. Abstract: Reaction energetics of the double (2H + /2e − ), i.e., the first 1H + /1e − (catechol → phenoxyl radical) and the second 1H + /1e − (phenoxyl radical → quinone) free radical scavenging mechanisms of quercetin and its six colonic catecholic metabolites (caffeic acid, hydrocaffeic acid, homoprotocatechuic acid, protocatechuic acid, 4-methylcatechol, and catechol) were computationally studied using density functional theory, with the aim to estimate the antiradical potency of these molecules. We found that second hydrogen atom transfer (HAT) and second sequential proton loss electron transfer (SPLET) mechanisms are less energy demanding than the first ones indicating 2H + /2e − processes as inherent to catechol moiety. The Gibbs free energy change for reactions of inactivation of selected free radicals indicate that catecholic colonic metabolites constitute an efficient group of more potent scavengers than quercetin itself, able to deactivate various free radicals, under different biological conditions. They could be responsible for the health benefits associated with regular intake of flavonoid-rich diet.